Strategi Peningkatan Kinerja Penyuluh dalam Mengembangkan Pertanian di Kecamatan Sesayap - Kurniasih, Nia; Fadilah, Siti Nur; Zulhafandi, Zulhafandi; Kurniati Sari, Nove; Normalasarie, Normalasarie (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
The process of agricultural development benefits greatly from agricultural extension activities, particularly when it comes to improving the knowledge, skills, and attitudes of the primary actors and business people. The purposes of the research were to measure the performance of agricultural extension workers and formulate the strategies to improve the performance of agricultural extension workers in Sesayap Sub-district Tana Tidung District. The data used were primary data and secondary data. The methods of analyzing the data used were Likert and SWOT analysis. The results of the research showed that the performance of agricultural extension workers in Sesayap Subdistrict was 62 with a good category and the strategies to improve the performance of agricultural extension workers in Sesayap Subdistrict were to implement the SO (Strength-Opportunities) strategy, namely: (a) Agricultural extension workers have good education with over two years of work to optimize technology and innovation. (b) The number of extension workers is sufficient, extension workers have enthusiasm and dedication to work and are able to utilize the existing facilities and infrastructure at BPP to enhance the ability and capacity of extension workers. (c) With adequate education of extension workers, the extension workers have enthusiasm and dedication to work and are relatively young so that they can optimize learning media through online.